ON QUASI-PERIODIC INTRINSIC LIGHT VARIABILITY IN A CLOSE SPECTROSCOPIC BINARY CX DRA - Pustylnik, I.; Kalv, P.; Harvig, V.; Aas, T. (Одеські астрономічні публікації, 2007)
Quasi-periodic light variations of bright spectroscopic emission-line binary CX Draconis were discovered based on observations at Tallinn Observatory in 1981-1990.